Factors determining intention to vaccinate against Covid-19: A developing nation perspective. Issue 2 (3rd July 2021) - Garg, Ruchi; Chhikara, Ritu; Chhabra, Sakhhi; Bhardwaj, Alok
Abstract: India is more challenged than developed nations in reducing the Covid-19 cases and lowering death rates due to the huge population and unprepared health care system. As intention to vaccinate is contextual and its availability does not translate into their de facto adoption., this paper examines the factors that determine intention to vaccinate against COVID-19 in India. A research model was tested using 222 responses was tested using structural equation modeling. Findings suggested that credibility and awareness positively impacted whereas vaccine hesitancy and perceived risk negatively influenced intention to vaccinate. The fear of side effects did not impact the intention to vaccinate.